A case of feline large granular lymphocyte lymphoma with complete remission and long survival by surgical resection and adjuvant nimustine administration. Issue 6 (17th August 2021) - Akiyoshi, Makoto; Akiyoshi, Masami
Abstract: A 7‐year‐old spayed female Scottish Fold cat presented with a 4‐week history of anorexia, weight loss and vomiting. Abdominal ultrasonography revealed a jejunal mass and a slightly enlarged jejunal lymph node. A fine‐needle aspiration of the mass revealed many round cells with multiple small intracytoplasmic magenta granules. The mass was diagnosed as a large granular lymphocyte (LGL) lymphoma based on cytology. The LGL lymphoma was completely resected via open surgery. The histologic and cytologic evaluations showed no neoplastic findings in the jejunal lymph node, liver, spleen, kidney or bone marrow. The LGL lymphoma was localized to the jejunum. Postoperatively, the cat received chemotherapy with nimustine, L ‐asparaginase and prednisolone. The cat is currently receiving nimustine every 6 weeks, without adverse events, and treatment has been administrated a total of 18 times up until day 552. The cat is in a good condition, and the LGL lymphoma has not recurred. Nimustine should be considered one of the effective chemotherapeutic agents in the treatment of feline LGL lymphoma cases in the future. Abstract : A case of feline large granular lymphocyte lymphoma with complete resection and nimustine: successful treatment .